Eastern Literature as Knowledge Field and Training: an Aesthetical and Philosophical Journey to the Teacher’s Practice - Pérez Uribe, Wilson (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Within the framework of professional practices at the Faculty of Education of University of Antioquia and its Literature and Spanish undergraduate program, this paper intends the understanding and ack- nowledgement of the formative experience that took place in the Eastern Literature Training research group –White Cherry ́s Workshop– and the reading aloud cycle –The Internal Time–, both of them being part of the degree project named “The Heart on the Tip of the Brush: Eastern Literature from an Esthetical and Philosophical Perspective as a Contribution to the Humanistic Education”. Both spaces are characterized as they acquire a formative sense, where the preservice teacher has the possibility to build pedagogical knowledge while teaching literature. Thus, it is raised the reflection on how the teacher, during their practices, interacts with some cultural, literary and historical knowledge. The con- clusion expected is that the practice, at the workshops’ sceneries in the training research group and the readings aloud, enables a reflection axis, construction of knowledge and inquiry, regarding other ways of thinking